A threatened new species of Ipomoea (Convolvulaceae) from the Brazilian Cerrado revealed by morpho-anatomical analysis - Diego Santos; Raysa Valéria Carvalho Saraiva; Tiago Massi Ferraz; Emília Cristina Pereira Arruda; Maria Teresa Buril (PhytoKeys, 2020)
A new species of Ipomoea, endemic to the Cerrado domain in Maranhão, Brazil, is described. Ipomoea maranhensis D.Santos & Buril, sp. nov. has been misidentified as I. burchellii Meisn. in several herbaria. Even though both species have oblong, pubescent leaves, they can be distinguished by morpho-anatomical characters. We present a diagnosis, complete description, illustration, taxonomic comments, conservation status and distribution map.